Antisense oligonucleotides-Laden UiO-66@Au nanohybrid for enhanced radiotherapy against hypoxic tumor by dual-inhibition of carbonic anhydrase IX. (December 2021) - Wang, Kai; Ding, Shuaishuai; Zeng, Lijuan; Zhou, Jingrong; Cao, Yuhua; Wu, Jiaqian; Lu, Lu; Bian, Xiu-wu; Tian, Gan
Highlights: A biodegradable MOF-based nanoplatform was designed for hypoxia-relief enhanced radiotherapy of triple negative breast cancer. A dual exogenous/endogenous CA IX inhibition strategy for hypoxia alleviation was proposed and realized. The dual CA IX inhibition synergized with Au-mediated radiosensitization to afford super management efficiency for hypoxic tumor . Abstract: Hypoxia-acquired radioresitance is considered to be a major factor responsible for the clinical failure of radiotherapy. Carbonic anhydrase IX (CA IX), a hypoxia-induced cell-surface enzyme involved in pH regulation of hypoxic solid tumors, has been acknowledged as a desirable target for cancer therapy. Herein, we developed a dual exogenous/endogenous CA IX inhibition strategy using core/satellite-like metal-organic framework (UiO-66)/gold nanoparticles (Au NPs) nanohybrids as a therapeutic platform for hypoxia-relief enhanced RT of triple negative breast cancer. The UiO-66 matrix supported the Au NPs generation in situ and would decompose inside tumor cells by the high-concentration phosphates to release p -phthalic acid (PTA), a original building skeleton of the UiO-66 matrix, to inhibit CA IX, while the decorated Au NPs served as radiosensitizers to potentiate the sensitivity of tumor cells to X-ray and yet provided active sites for CA IX antisense oligonucleotide (ASO) loading via formation of stable Au-S bond to knockdown CA IX. The dual inhibitory manner, exogenous inhibition from PTA and endogenous inhibition from CA IX ASO, largely alleviated the hypoxia-induced resistance and synergized with Au NPs-mediated radiosensitization to afford super therapeutic outcome in vitro and in vivo, supporting the feasibility of our synergistic RT strategy in hypoxic tumor management. Graphical abstract: Image, graphical abstract